Modifying the health system to maximize voluntary medical male circumcision uptake: a qualitative study in Botswana - Semo BW (Dove Medical Press, 2017)
Bazghina-Werq Semo,1,2 Kathleen E Wirth,1–4 Conrad Ntsuape,5 Scott Barnhart,1 Nora J Kleinman,1,2,6 Nankie Ramabu,2 Jessica Broz,2 Jenny H Ledikwe1,2 1Department of Global Health, University of Washington, Seattle, WA, USA; 2Botswana International Training and Education Center for Health (I-TECH), Gaborone, Botswana; 3Department of Epidemiology, Harvard T.H. Chan School of Public Health, Boston, MA, USA; 4Department of Immunology and Infectious Diseases, Harvard T.H. Chan School of Public Health, Boston, MA, USA; 5Department of HIV/AIDS Prevention and Care, Botswana Ministry of Health, Gaborone, Botswana; 6NJK Consulting, Seattle, WA, USA Background: In 2007, the World Health Organization and the Joint United Nations Programme on HIV/AIDS endorsed voluntary medical male circumcision (VMMC) as an add-on HIV-prevention strategy. Similar to many other sub-Saharan countries, VMMC uptake in Botswana has been low; as of February 2016, only 42.7% of the program target had been achieved. Previous work has examined how individual-level factors, such as knowledge and attitudes, influence the update of VMMC. This paper examines how factors related to the health system can be leveraged to maximize uptake of circumcision services, with a focus on demand creation, access to services, and service delivery. Methods: Twenty-seven focus group discussions with 238 participants were conducted in four communities in Botswana among men (stratified by circumcision status and age), women (stratified by age), and community leaders. A semi-structured guide was used by a trained same-gender interviewer to facilitate discussions, which were audio recorded, transcribed, translated to English, and analyzed using an inductive analytic approach. Results: Participants felt demand creation activities utilizing age- and gender-appropriate mobilizers and community leaders were more effective than mass media campaigns. Participants felt improved access to VMMC clinics would facilitate service uptake, as would designated men’s clinics with male-friendly providers for VMMC service delivery. Additionally, providing comprehensive pre-procedure counseling and education, outlining the benefits and disadvantages of the surgical procedure, and explaining the differences between the surgical and non-surgical procedures, were suggested by participants to increase understanding and uptake of VMMC. Conclusion: Cultural acceptability of circumcision services can be improved by engaging age- and gender-appropriate community mobilizers. Involving influential community leaders, providing a forum for men to discuss health issues, and bringing services closer to people can increase VMMC utilization. Service delivery can be improved by communicating the pros and cons of the procedure to the clients for informed decision-making. Keywords: HIV, demand creation, service delivery, sub-Saharan Africa